Digital Competences Relationship between Gender and Generation of University Professors - Basantes Andrade, Andrea Verenice (2020)
Digital competences can be defined as the set of techno-pedagogical and communicational skills that allow teachers to function effectively within the educational contexts that new technologies generate. This research work was aimed to establish the relationship between the level of university professors’ digital competences concerning their gender and generation. The study was based on a sample of 613 professionals with an undergraduate degree, who came from different areas of Ecuador; they were the attendees to the "Training Program for Leveling Tutors using Virtual Modality" at Técnica del Norte University (Ibarra -Ecuador). This research applied a quantitative and explanatory approach where the non-parametric statistical test of Chi-square was used to corroborate the validity of the data; it was obtained from a survey applied to the participants in this training course. The results show that the level of digital competences is gender independent but generation dependent. Generation Z is the one with the best digital capabilities, with an average of 61.14%. Regarding the gender, a dependence is observed only with two out of five groups of competencies analyzed in this study; the cloud storage and the interaction of social network. The research line of digital competences is extensive, the results should not be generalized or extrapolated without considering the characteristics of the educators and the context, it is suggested to assess the teaching staff digital competencies, considering other types of demographic variables, so that higher education institutions can carry out a comprehensive training planning in digital skills.